Tailored Approach in Inguinal Hernia Repair – Decision Tree Based on the Guidelines - Köckerling, Ferdinand; Schug-Pass, Christine (Frontiers in Surgery, 2014)
The endoscopic procedures TEP and TAPP and the open techniques Lichtenstein, Plug and Patch and PHS currently represent the gold standard in inguinal hernia repair recommended in the guidelines of the European Hernia Society, the International Endohernia Society and the European Association of Endoscopic Surgery. 82 % of experienced hernia surgeons use the "tailored approach", the differentiated use of the several inguinal hernia repair techniques depending on the findings of the patient, trying to minimize the risks. The following differential therapeutic situations must be distinguished in inguinal hernia repair: unilateral in men, unilateral in women, bilateral, scrotal, after previous pelvic and lower abdominal surgery, no general anaesthesia possible, recurrence and emergency surgery. Evidence-based guidelines and consensus conferences of experts give recommendations for the best approach in the individual situation of a patient. This review tries to summarized the recommendations of the various guidelines and to transfer them into a practical dicision tree for the daily work of surgeons performing inguinal hernia repair.